Radiocarbon dating of Bestansur and Shimshara - Flohr, P; Matthews, R; Matthews, W; Richardson, A; Fleitmann, D; Matthews, W; Richardson, A (Oxbow Books, 2020)
In this chapter we present eleven 14C dates from Bestansur and one from Shimshara, and discuss them in relation to the previously published Sheikh-e Abad and Jani dates (Matthews et al. 2013c) and the wider context. The Bestansur and Shimshara samples were all analysed by Beta Analytic laboratories. The samples, their contexts and the results are provided in Table 11.1. All 14C dates were calibrated in OxCal version 4.3 using the IntCal13 curve (Bronk Ramsey 2009; Reimer 2013). All dates referred to throughout this chapter, and the entire volume, are calibrated BC dates unless otherwise stated.